HIPERPORNOGRAFI PEREMPUAN DALAM IKLAN - Ervan Ismail (Universitas Mercu Buana, 2015)
Research by the author is using the critical paradigm is based on the notion that a variety of issues related to the hyper-pornography emerged from the audience understandings of social reality constructed by advertising. Type of research is a descriptive study using semiotic analysis. Data was collected to make a second record Geliga Muscle Cream ads and Malkis Abon as primary data. Secondary data obtained through the study of literature in the form of books, journals and internet sites.In the second survey results revealed the ad has a depth of meaning that leads to hyper-pornography completely after carefully using the theory of Jean Baudrillard was found that the two ads is the result of the simulation and produce effects that lead women toward kekecenderungan hiperpornografi, based on the results of the study, the second theme ad lifting sensation will be a sign that women's sexuality is the most dominant in the second ad. This advertising system refers to Hollywood movies, one movie Devil Wear Prada and also a novel by Tami Hoag